Socialization and Counseling of Using Social Media for Marketing Salted Fish at Palembang Salted Fish Center (Siabang) - Erni Purbiyanti; Utan Sahiro Ritonga; Susi Lestari (Media Publikasi Cendekia Indonesia, 2026)
This community service activity aims to empower salted fish artisans at the Palembang Salted Fish Center (SIABANG) by providing outreach and training on the use of social media as a marketing tool for their products. The activity focused on basic digital marketing, including techniques for utilizing Facebook as a promotional platform, creating engaging content, using hashtags, scheduling posts, and implementing AI-based technology to support marketing efforts. This activity was implemented using an Asset-Based Communities Development (ABCD) approach that emphasizes identifying and strengthening the artisan community's existing assets. The effectiveness of the activity was measured through a pre- and post-test using five knowledge indicators: posting time, content types and elements, hashtag use, content schedule planning, and the use of AI applications. Evaluation results showed that participants' understanding improved across all indicators, particularly regarding the use of AI technology for narrative creation and marketing content, which increased from 8 to 11 participants who answered correctly. However, several challenges remained related to the use of social media analytics and more effective content planning. Nevertheless, this training had a positive impact, enabling artisans to reduce their dependence on middlemen and market their salted fish products independently through social media